2008
DOI: 10.1080/10826080801914402
|View full text |Cite
|
Sign up to set email alerts
|

Butch/Femme Differences in Substance Use and Abuse Among Young Lesbian and Bisexual Women: Examination and Potential Explanations

Abstract: The current study examined the role of gender atypical self-presentation on the alcohol, tobacco, and marijuana use, as well as symptoms of substance abuse, of an ethnically diverse sample of 76 young (ages 14 – 21 years) lesbian and bisexual women who were interviewed between 1993-95 in New York City. Even after controlling for age, sexual identity, and social desirability, young butch women reported drinking alcohol more frequently and in greater quantity, smoking more cigarettes, and using marijuana more fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 45 publications
5
45
1
Order By: Relevance
“…Risk factors identified in this review that could be considered unique to sexual minorities include internalised homophobia,46 reactions to disclosure of sexual orientation,87 and identity within sexual minority communities (eg, ‘goth’ identity or presentation of masculinity/femininity) 67 80. Research conducted after the search time for the present review indicates some evidence for smoking risk based on presentation of masculinity or femininity,88 which is compatible with historical scholarship 89.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Risk factors identified in this review that could be considered unique to sexual minorities include internalised homophobia,46 reactions to disclosure of sexual orientation,87 and identity within sexual minority communities (eg, ‘goth’ identity or presentation of masculinity/femininity) 67 80. Research conducted after the search time for the present review indicates some evidence for smoking risk based on presentation of masculinity or femininity,88 which is compatible with historical scholarship 89.…”
Section: Discussionsupporting
confidence: 69%
“…In contradiction with those findings, Willoughby and colleagues did not find an association between smoking and family rejection 73. An array of risks were examined, from religiosity being protective against smoking among heterosexual adolescents but not sexual minority adolescents,79 to bisexual women having greater odds of smoking for weight control than lesbian women,25 to differential associations of smoking among subcultures of sexual minority populations 67 80…”
Section: Resultsmentioning
confidence: 92%
“…For instance, Willoughby, Lai, Doty, Mackey, and Malik (2008) found that, in a sample of gay men, self-identified subgrouping categories (e.g., Goths, Twinks, Bears) differentiated prevalence of current (i.e., once in past 30 days) smoking. Rosario, Schrimshaw, and Hunter (2008) noted that among lesbians, women who identified as butch (i.e., more masculine) tended to smoke more than women who identified as femme (i.e., more feminine). Clearly, there are details in the divisions, and future studies should strive to innovatively seine and disentangle critical information from the oft-combined lesbian, gay, and bisexual identities in sexual minority research.…”
Section: Discussionmentioning
confidence: 99%
“…29 Counter to the literature, indicators of masculine and feminine identity were not associated with smoking behaviors. 30 This lack of association may be due to sample characteristics or measurement issues. Study findings should be replicated using validated measures of masculinity/femininity and gender identity.…”
Section: Matthews Et Almentioning
confidence: 99%